Roman Charity Queer Lactations in Early Modern Visual Culture - Gisela Sperling, Jutta (Image, 2016)
»Roman Charity« investigates the iconography of the breastfeeding daughter from the perspective of queer sexuality and erotic maternity. The volume explores the popularity of a topic that appealed to early modern observers for its eroticizing shock value, its ironic take on the concept of Catholic »charity«, and its implied critique of patriarchal power structures. It analyses why early modern viewers found an incestuous, adult breastfeeding scene »good to think with« and aims at expanding and queering our notions of early modern sexuality. Jutta Gisela Sperling discusses the different visual contexts in which »Roman Charity« flourished and reconstructs contemporary horizons of expectation by reference to literary sources, medical practice, and legal culture.